The martian - Scott, Ridley; Damon, Matt; Chastain, Jessica (Los Angeles, California : Twentieth Century Fox, 2015)
During a manned mission to Mars, American astronaut Mark Watney is presumed dead and left behind by his crew. But Watney is still alive, and he must now find a way to contact Earth and survive on a barren planet with meager supplies in the hope that an international team of scientists can devise a near-impossible rescue plan to bring him home.
Based upon the novel by Andy Weir.
Executive producer, Drew Goddard ; director of photography, Dariusz Wolski ; film editor, Pietro Scalia.
Matt Damon, Jessica Chastain, Kristen Wiig, Jeff Daniels, Michael Pena, Kate Mara, Sean Bean, Sebastian Stan, Aksel Hennie & Chiwetel Ejiofor.
LPF: P13
DVD format ; Region 3, Dolby Digital.
In English with optional English, Malay and Mandarin subtitles.
Keywords: Astronauts -- Drama; Survival -- Drama; Science fiction films